AN ANALYSIS OF FACTORS INFLUENCING CUSTOMERS’ ACCEPTANCE OF SMART RESTAURANTS IN JAKARTA, INDONESIA. - Yuwono, Daniel; Supandi, Sophan; Anggiani, Sarfilianty (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
Technology is becoming an essential element of business operations, and the restaurant industry is no exception. With the support of technology, smart restaurants have emerged in the food and beverage industry. This study investigates the linkage between customers’ acceptance (CA) level and smart service competencies in the Food and Beverage sector across Jakarta, as part of the technology acceptance model (TAM). The study applies a quantitative approach and convenience sampling technique to draw the samples. The data were gathered from 117 respondents and structural equation modeling was used to analyze data. Smart PLS (Partial Least Square) was used for the tool analysis. The results of this study indicate that the CA of smart restaurants was influenced by perceived of enjoyment (PE), perceived ease of use (PEOU), and perceived of price (PV). However, perceived of security (PS) does not relate to CA.